The Weekly Ward Review by the Consultant on the General Adult Inpatient Wards in Mersey Care NHS Foundation Trust – How Are We Doing? Do We Need to Improve the Patient Experience? - Ankita Vinjamuri; Jonathan Tjong A Tjoe; Ranjan Baruah; Roweida Sammour; Declan Hyland (BJPsych Open)
Aims: Ward reviews are a pivotal component of patient care in psychiatric inpatient settings, offering a structured opportunity for patients to engage with their treatment team and contribute to their treatment plan. Ward reviews are essential for discussing treatment progress, making necessary adjustments to care plans, and addressing patient concerns. The aim of this quality improvement project was to assess and improve the experience of ward reviews for inpatients on the Trust’s general adult inpatient wards by ensuring inpatients are well-informed about the timing of and attendees for their ward reviews and help them prepare effectively for their ward review.